Global brand strategy : world-wise marketing in the age of branding - Steenkamp, Jan-Benedict E. M. (Palgrave Macmillan, 2017)
What sets strong global brands apart? First, they generate more than half their revenue and most of their growth outside their home market. Secondly, their brand equity is responsible for a massive percentage of their firm's market value. Third, they operate as single brands everywhere on the planet. We find them in B2C and B2B industries, among large and small companies, and among established companies and new businesses. The stewards of these brands have a set of skills and knowledge that sets them apart from the typical corporate marketer. So what's their secret? In a world that is globalizing, but not yet globalized, how do you build a powerful global brand that resonates universally but also accommodates local nuances? How do you ensure that it is dynamic and flexible enough to change at market speed? World-class marketing expert Jan-Benedict Steenkamp has studied global brands for over 25 years on six continents. He has distilled their practices into eight tools that you can start using today. With case studies from around the world, Steenkamp introduces the global brand value chain and explains how brand equity factors into shareholder value. Provocative and timely, Global Brand Strategy will equip executives with techniques for developing strategy, organizing execution, and measuring results so that your brand will prosper globally. The book speaks to three types of B2C and B2B managers: those who want to strengthen already strong global brands, those who want to launch their brands globally and get results, and those who need to revive their global brand and stop the bleeding.
Keywords: Brand name products -- Planning.; Branding (Marketing); Brand name products -- Management.; Export marketing.; elektronické knihy; electronic books